The AI Co-Author: Investigating the Impact of Generative AI on Creative Short Story Writing Skills on the Students of English Education Study Program - Christmas Prasetia Ate; Dortean Amelia Jois Jaha (Journal of Innovative Technologies in Learning and Education, 2026)
This qualitative case study investigates the impact of Generative AI (GenAI) as a "co-author" on the creative short story writing skills of 19 fourth-semester students in the English Education Study Program at Citra Bangsa University. Amidst the growing debate on AI in education, this study explores how EFL learners utilize tools like ChatGPT to overcome challenges such as blank page syndrome and limited lexical resources. Data were collected through semi-structured interviews, reflective journals, and analysis of digital artifacts (chat logs and story drafts) following a six-week creative writing workshop. The findings reveal that GenAI significantly reduced writing anxiety by serving as an ideation partner and expanded students' descriptive vocabulary through context-specific synonyms. However, the study also highlights a complex negotiation of authorship, where students acted as "creative directors," curating AI outputs to ensure cultural relevance and narrative voice. The research concludes that integrating GenAI requires a pedagogical shift from product-oriented to process-oriented assessment, emphasizing "prompt engineering" as a critical new literacy for future English teachers